Manajemen Proyek Pembuatan Jam Dinding Aesthetic (Berbasis Kardus Bekas) - Nico Fernando; Toni Ong; Vikhri Septama Deni; Vanness Kangnanda (Universitas 17 Agustus 1945, 2022)
ERP is an aspect that is very necessary for many leading or advanced companies today, one of which is PT Unilever Indonesia. The purpose of this analysis is to determine the influence of the ERP system on supply chain management at PT Unilever Indonesia. The method used is a qualitative method with data sourced from journals and the internet. This analysis shows the benefits of the ERP system for Unilever companies after implementing ERP.